2006
DOI: 10.1111/j.1469-8137.2006.01836.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of short‐term dynamics in carbon isotope ratios of ecosystem respiration (δ13CR) in a Mediterranean oak woodland and linkage to environmental factors

Abstract: Summary• Temporal dynamics in carbon isotope ratios of ecosystem respiration ( δ 13 C R ) were evaluated on hourly, daily and annual timescales in a Mediterranean woodland. Emphasis was given to the periods of transition from wet to dry season and vice versa, when the system turns from a net carbon sink to a source. The constancy of nocturnal δ 13 C R was tested.• The relationship between δ 13 C R (determined through Keeling plots) and environmental factors was evaluated through time-lag analysis.• δ 13 C R ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 74 publications
5
65
1
Order By: Relevance
“…Soil and ecosystem δ 13 C R are indeed often well correlated with environmental factors driving changes in photosynthetic discrimination during the preceding days (e.g. Ekblad and Högberg, 2001;Werner et al, 2006). The rapid transfer of photosynthates to roots, root exudates and subsequent respiration in the rhizosphere has been demonstrated by 13 C labelling experiments (e.g.…”
Section: M32mentioning
confidence: 93%
See 2 more Smart Citations
“…Soil and ecosystem δ 13 C R are indeed often well correlated with environmental factors driving changes in photosynthetic discrimination during the preceding days (e.g. Ekblad and Högberg, 2001;Werner et al, 2006). The rapid transfer of photosynthates to roots, root exudates and subsequent respiration in the rhizosphere has been demonstrated by 13 C labelling experiments (e.g.…”
Section: M32mentioning
confidence: 93%
“…The information on dynamics of ecosystem respiration (δ 13 C R assessed by Keeling-plot approaches) presents again a very heterogeneous picture: while Ogée et al (2003) and Schnyder et al (2004) found only minor nocturnal variation of δ 13 C R (<3 ‰), others report that nocturnal ecosystem δ 13 C R presented the largest variation among different respiratory components (Kodama et al, 2008;Unger et al, 2010a). Nocturnal variations in δ 13 C R were 6.4 ‰ in a grassland (Bowling et al, 2003), 4.2-8.1 ‰ in a Mediterranean woodland (Werner et al, 2006;Unger et al, 2010a), 6.1 ‰ in a Pinus sylvestris stand (Kodama et al, 2008), 2.6-3.6 ‰ in a subalpine forest (Bowling et al, 2005;Riveros-Iregui et al, 2011), and 3.8 ‰ a beech-dominated deciduous forest (24 h-cycle, Knohl et al, 2005).…”
Section: New Methodsological Developments In High Time-resolved Measurmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar investigations in boreal, temperate and Mediterranean forest ecosystems have shown time lags ranging between 0 and 10 days (Bowling et al, 2002;Knohl et al, 2005;Werner et al, 2006;Ekblad and Hogberg, 2001;McDowell et al, 2004;Mortazavi et al, 2005). It is important to note that at these forest ecosystems the diversity of species per unit area is very low, whereas the forests of Central Amazonia have more than 200 species ha −1 (Oliveira and Mori, 1999;Oliveira and Amaral, 2004;Oliveira and Amaral, 2005 (Fig.…”
Section: Correlation Between δ 13 C Reco and Dmentioning
confidence: 98%
“…The stable C isotopic composition (d 13 C) of ecosystem respired CO 2 (d 13 C R ) is an important parameter for application in isotope-based C budget models and understanding the controls over terrestrial C exchange processes (e.g., McDowell et al 2004a). d 13 C R is known to vary seasonally with changes in photosynthetic discrimination and respiratory activity (e.g., Bowling et al 2001Bowling et al , 2002Griffis et al 2004;Ponton et al 2006;Werner et al 2006Werner et al , 2007aAlstad et al 2007;Schaeffer et al 2008). Recent studies showed small (Ogée et al 2003;Still et al 2003;Schnyder et al 2004) to large ([6%; e.g., Bowling et al 2003;Werner et al 2006;Kodama et al 2008) variation in d 13 C R even within a single night.…”
Section: Introductionmentioning
confidence: 99%